The influence of internal actors on the sophistication of costing systems in Tunisia / Hanen Moalla and Chedli Basti - Moalla, Hanen; Basti, Chedli (Accounting Research Institute (ARI), 2020)
This research investigated the extent to which internal actors influence the sophistication of costing systems in Tunisia. It is based on Rogers' Theory (1995) and the theoretical perspectives of Abrahmson (1991) explaining the diffusion of administrative technologies. The empirical study was conducted using a questionnaire given to 65 management accountants in Tunisia. The role of internal actors was investigated through the competence of the costing system manager, top management support, resistance to change, and membership in a group. The findings show that competence, membership in a group, and top management support positively affect the sophistication of costing systems, while, resistance to change blocks the adoption of management accounting innovations like activity-based costing (ABC). This study is the first piece of research that investigated the relationship between the role of internal actors and the sophistication of costing systems. It contributes to the management accounting research as it is one of the few studies conducted in developing countries and dealing with management accounting characteristics. Previous research was limited either to the factors affecting the adoption of ABC or conducted in developed countries. This study can be useful for managers when choosing a costing system and defining its characteristics.